PENGGUNAAN MEDIA INFORMASI SEBAGAI PENDUKUNG KINERJA STAF (Studi Deskriptif pada Dinas Pendidikan dan Kebudayaan Kota Pagaralam) - Dodi Antonyus (DIADIK, 2021)
The objectives of this study are to: 1). Describe an overview of the use of information media in supporting the performance of staff at the Pagar Alam City Education and Culture Office. 2). Describe what office technologies have been used to support staff performance at the Pagar Alam City Education and Culture Office. 3). Describe the positive and negative impacts of the use of technology-based information media at the Pagar Alam City Education and Culture Office. The approach used in this study is a qualitative approach. The type of method used in this research is a case study, this research seeks to explain and try to describe and study the use of information media as a support for staff performance at the Pagar Alam City Education and Culture Office. Subjects / respondents in this study were all employees / staff at the Education and Culture Office of Pagar Alam City. The data collection techniques used were interviews, observation, Focus Group Discussion and Documentation. The data collected in this study is data in qualitative form, so it uses qualitative data analysis. The results of the study contain a description of the use of information media in the scope of computer-based information technology in supporting staff / employee performance. Some of the advantages of using information media in the Pagar Alam Disdikbud office are: saving costs, saving time and effort, facilitating control and accuracy, facilitating supervision, producing better and tidier work, more information loaded, reducing boredom with manual methods, reduce employee fatigue